Comparison of Fast and Time Blood Glucose Levels in Chronic Disease Management Program Patients (Proalnic) and Non-Prolanic with Diabetes Mellitus in Praya Health Center - Aini, Miftahul; Tatontos, Erlin Yustin; Inayati, Nurul; Pauzi, Iswari (THRIVE Health Science Journal, 2024)
Glucose is the most important carbohydrate which is mostly absorbed into the bloodstream as glucose and other sugars are converted into glucose in the liver. Blood glucose levels are closely related to DM. Prolanic (Chronic Disease Management Program) is a health service system that involves participants from Health Facilities and BPJS health in the context of health care for participants suffering from chronic diseases including diabetes mellitus to achieve optimal quality of life with cost-effective and efficient health services. To determine the comparison of fasting and intermittent blood glucose levels in prolanic and non-prolanic patients suffering from DM at Praya Health Center. : This type of research is Analytical Observation, the sample is taken purposively. A sample of 30 respondents, in this study were 15 respondents who took prolanis and 15 respondents who did not follow prolanis who had a history of diabetes mellitus and underwent blood glucose level checks at the UPTD BLUD Laboratory of Praya Health Center. Based on research that has been done, the average fasting blood glucose level in prolanis is 158 mg/dl and fasting glucose is 204 mg/dl. Meanwhile, non-prolanic fasting glucose levels are 156 mg/dl and fasting glucose levels are 204 mg/dl.